ROLE OF CYP1B1 GENE POLYMORPHISM IN THE DEVELOPMENT OF POSTMENOPAUSAL OSTEOPOROSI - Игорь Сергеевич Захаров; Вадим Гельевич Мозес; Галина Александровна Ушакова; Глеб Иванович Колпинский; Андрей Николаевич Глушков; Людмила Александровна Гордеева; Елена Владимировна Рудаева (Медицина в Кузбассе)
Objective – to study the role of polymorphism (Leu432Val, rs1056836) of the CYP1B1 gene in the development of postmenopausal osteoporosis.